Boron Substituted Na3V2(P1−xBxO4)3 Cathode Materials with Enhanced Performance for Sodium‐Ion Batteries. Issue 12 (2nd August 2016) - Hu, Pu; Wang, Xiaofang; Wang, Tianshi; Chen, Lanli; Ma, Jun; Kong, Qingyu; Shi, Siqi; Cui, Guanglei
Abstract : The development of excellent performance of Na‐ion batteries remains great challenge owing to the poor stability and sluggish kinetics of cathode materials. Herein, B substituted Na3 V2 P3 –x B x O12 (0 ≤ x ≤ 1) as stable cathode materials for Na‐ion battery is presented. A combined experimental and theoretical investigations on Na3 V2 P3 –x B x O12 (0 ≤ x ≤ 1) are undertaken to reveal the evolution of crystal and electronic structures and Na storage properties associated with various concentration of B. X‐ray diffraction results indicate that the crystal structure of Na3 V2 P3 –x B x O12 (0 ≤ x ≤ 1/3) consisted of rhombohedral Na3 V2 (PO4 )3 with tiny shrinkage of crystal lattice. X‐ray absorption spectra and the calculated crystal structures all suggest that the detailed local structural distortion of substituted materials originates from the slight reduction of V–O distances. Na3 V2 P3‐1/6 B1/6 O12 significantly enhances the structural stability and electrochemical performance, giving remarkable enhanced capacity of 100 and 70 mAh g −1 when the C‐rate increases to 5 C and 10 C. Spin‐polarized density functional theory (DFT) calculation reveals that, as compared with the pristine Na3 V2 (PO4 )3, the superior electrochemical performance of the substituted materials can be attributed to the emergence of new boundary states near the band gap, lower Na + diffusion energy barriers, and higher structure stability. Abstract : Electrochemical performance and local crystal strucure of B substituted Na3 V2 P3 –x B x O12 are investigated experimentally and theoretically. Compared to pristine Na3 V2 (PO4 )3, B substituted Na3 V2 P3 –x B x O12 cathode offers better cycling stability and rate capability thus improves the electrochemical performance significantly.